School Crime and the Patterns of Roles of School Resource Officers: evidence From a National Longitudinal Study - Fisher, Benjamin W. (Crime & delinquency, 2020)
This study used national-level two-wave longitudinal data from school principals (N = 850) to examine whether and the extent to which implementing school resource officers (SROs) with varying role profiles related to changes in crime recorded in schools and reported to police. We identified three common role profiles of SROs: Low Engagement, Full Triad, and Reactionary. Implementing SROs engaged primarily in law enforcement (i.e., Reactionary SROs) predicted increases in recording nonserious violent and property crimes and a decrease in reporting drug crime to the police, respectively. Implementing Full Triad SROs who were also engaged in additional roles (e.g., mentoring) predicted a reduction in recording nonserious violent crimes, but an increase in recording property crimes and reporting crime to law enforcement.